What do people think about genetic engineering? A systematic review of questionnaire surveys before and after the introduction of CRISPR - Ramos, Pedro Dias; Almeida, Maria Strecht; Olsson, Ingrid Anna Sofia (Frontiers in Genome Editing, 2023)
The advent of CRISPR-Cas9 in 2012 has come to revolutionize the field of genetics by broadening the access to a method for precise modification of the human genome. It also brought renewed attention to the ethical issues of genetic modification and the societal acceptance of technology for this purpose. So far, many surveys assessing public attitudes towards genetic modification have been conducted worldwide. Here we present the results of a systematic review of primary publications of surveys addressing public attitudes towards genetic modification as well as awareness and knowledge about the technology. A total of 53 primary publications focusing on applications in humans and non-human animals were identified covering countries in 4 continents. The 30 studies from until 2012 (pre-CRISPR) address gene therapy in humans and genetic modification of animals for food production and for biomedical research. The 23 studies from after 2013 (CRISPR) address gene editing in humans and animals. Across countries, respondents see gene therapy for disease treatment or prevention in humans as desirable and highly acceptable, whereas enhancement is generally met with opposition. When the study distinguishes between somatic and germline applications, somatic gene editing is generally accepted whereas germline applications are met with ambivalence. The purpose of the application is also important for attitude to genetically modified animals: modification in food production is much less accepted than for biomedical application in pre-CRISPR studies. A relationship between knowledge/awareness and attitude to genetic modification is often present. A critical appraisal of methodology quality in the primary publications as regards to sampling as well as questionnaire design, development, administration shows that there is considerable room for improvement in the reporting of methodological detail. Lack of information is more common in earlier studies, which probably reflects the changing practice in the field.